Utilização da lignina modificada na substituição parcial de fenol em adesivos fenólicos aplicados em laminados de madeira - Krindges, Andrini (2025)
This study investigates the principles of circular economy applied to lignin, a residue generated in the industrial process of pulp and paper production. The main objective is to explore the potential of lignin as a partial substitute for phenol in the synthesis of phenolic adhesives, comparing them with commercial adhesives. For this purpose, two pre-polymerization methodologies were adopted, using kraft lignin as a reference, in order to evaluate possible improvements in the synthesis process. The lignins were characterized by means of FTIR, ¹³C and ¹H NMR analyses. In FTIR, all spectra presented similar chemical groups, but in the phenolated lignins, exclusive vibrations were observed in the regions of 691 and 758 cm⁻¹, attributed to the addition of phenol molecules to lignin by reaction in the α-hydroxyl groups in the ortho or para positions. In the ¹³C NMR, all lignins presented guaiacyl and syringyl units, while the phenolated lignins also exhibited p-hydroxyphenyl units, identified in the regions of 129.4 and 126.1 ppm. The β-O-4 bond was detected only in the hydroxymethylated lignin, which also showed higher amounts of methoxyls compared to the others. For the phenolic adhesives, ¹³C NMR spectra were performed with 25% substitution of phenol for lignin, comparing them with the commercial adhesive. The results indicated similarity between all spectra and the commercial adhesive (FF-0%), evidencing that the crosslinking of the adhesive was not significantly altered by the substitution of phenol for lignin. To validate the use of lignin in the phenolic adhesives, plywoods were produced with substitutions of 25% and 50% of phenol for lignin. The results showed that both substitutions met the requirements of NBR 12466-2, highlighting the potential of lignin as a sustainable alternative to phenol. The FFL-25% sample showed the best performance under vacuum/pressure conditions, even surpassing the commercial sample in terms of fiber strength. The plywood sample with FFLF-50% resin showed superior performance in relation to the other 50% substitutions, with results equal to or superior to the FFLH-25% and FFL-25% samples. Overall, the study demonstrates the potential application of lignin as a partial substitute for phenol in the production of phenolic adhesives, providing environmental gains and contributing to the development of more sustainable and competitive products.